2010
DOI: 10.1186/1472-6920-10-65
|View full text |Cite
|
Sign up to set email alerts
|

Graduates from a reformed undergraduate medical curriculum based on Tomorrow's Doctorsevaluate the effectiveness of their curriculum 6 years after graduation through interviews

Abstract: BackgroundIn 1996 Liverpool reformed its medical curriculum from a traditional lecture based course to a curriculum based on the recommendations in Tomorrow's Doctors. A project has been underway since 2000 to evaluate this change. This paper focuses on the views of graduates from that reformed curriculum 6 years after they had graduated.MethodsBetween 2007 and 2009 45 interviews took place with doctors from the first two cohorts to graduate from the reformed curriculum.ResultsThe interviewees felt like they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 29 publications
1
15
0
3
Order By: Relevance
“…It cannot just be assumed they will see the relevance that may be obvious to those designing the course; for example it has also been shown that many Liverpool students do not realise that they have ample opportunity to practice academic medicine within the Liverpool curriculum because the opportunities are not signposted as such 17 and students can struggle without explicit 'signposts' to learning objectives. 18 Strengths and limitations of study There are of course some limitations to these focus groups. They did take place at different times in the year and thus each group of students had a different set of clinical experiences from their third year when starting the block and perhaps then saw the placement in a different context.…”
Section: Discussionmentioning
confidence: 99%
“…It cannot just be assumed they will see the relevance that may be obvious to those designing the course; for example it has also been shown that many Liverpool students do not realise that they have ample opportunity to practice academic medicine within the Liverpool curriculum because the opportunities are not signposted as such 17 and students can struggle without explicit 'signposts' to learning objectives. 18 Strengths and limitations of study There are of course some limitations to these focus groups. They did take place at different times in the year and thus each group of students had a different set of clinical experiences from their third year when starting the block and perhaps then saw the placement in a different context.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты исследований показывают, что применение методик полезно для обучения как медицинских работников, так и координаторов, менеджеров здравоохранения, принимающих решения. Преодоление барьера боязни перемен позволит преуспеть на чрезвычайно плодотворном пути моделирования, позволит предложить новые программы и гипотезы для исследований [1,19,33,34,35].…”
Section: принципы организации симуляционногоunclassified
“…Faktor lain yang cukup penting adalah bagaimana proses PBL hybrid dilaksanakan, misalnya apakah tes yang digunakan untuk menentukan kelulusan mahasiswa cukup mampu untuk memacu kemampuan belajar mandiri mahasiswa. Penelitian lain yang dilakukan di Inggris, meneliti tentang persepsi dokter lulusan kurikulum PBL tentang diri mereka, menyatakan bahwa dokter-dokter lulusan PBL merasa mempunyai kemampuan belajar mandiri yang cukup, dan merasa dipersiapkan dengan baik untuk menjadi seorang dokter (Watmough, O'Sullivan & Taylor, 2010).…”
Section: Hasil Dan Pembahasanunclassified